USULAN PERBAIKAN KUALITAS PRODUKSI ALUMINIUM TUBE BEROCCA ORG (ORANGE) 15AU DENGAN ALAT BANTU STATISTIK SEVEN TOOLS (STUDI KASUS DI PT. XYZ) - denny denny Denny Siregar; Kristin Samdamery (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2018)
The research about PT. XYZ which is one of the companies engaged in the field of packanging. The problem in this research is because of the increasing number of defect aluminum tube Berocca Org (Orange) 15 AU for the last four months that exceed the tolerance limits set by the company that is equal to 1.7% of the amount of production each month, therefore need improvement Quality products in the company. The objectives of this research are 1) to know the dominant defect type on Berocca Org (Orange) 15 AU product in finishing part 2) Find the root of the most important problem from the dominant defect type of Berocca Org (Orange) 15 AU 3) Recommend the improvement proposal to decrease Percentage defect on Berocca Org (Orange) 15 product material. The method used is to use tool of statistical seven tools that check sheet,pareto chart, p-chart and fishbone diagram. The results of the study were 1) Type of donation defect on Berocca Org (Orange) 15 AU product ie melet, stripes and eyes. 2) The root problem of the melet defect is that there is no routine time for maintenance and replacement per spring. The root of the most important problem of defect stripes is tired printing operators and printing operator's assistants lack the focus of stirring ink. Furthermore, the root of the most important problem of eye defect is the absence of clear and detailed SOP to check the printout. 3) Proposed improvements to reduce the percentage of defect is to perform maintenance (preventive maintenance) on a regular basis and scheduled to the machine and engine components for the duration of its life, to train new operators to operate the printing machine, controlling and adding alarms in the setting reads every A certain time for the operator's assistant to check and stir the printing ink,makin work instructions for controlling the printing process.